Comparison of glucose degradation product and receptor levels in diabetic and normal pregnancy - Şimşek Tanin, Özlem (J Turk Ger Gynecol Assoc, 2021)
OBJECTIVE: The aim of this study was to assess the diagnostic values of new biochemical markers that may be an alternative to the oral glucose tolerance test (OGTT) and determine the differences in these markers among three groups of women with varying degrees of glucose homeostasis dysregulation. MATERIAL AND METHODS: This was a prospective study. All women were screened with 50 gram (g) oral glucose and a 100 g OGTT for gestational diabetes mellitus (GDM). The patients were divided into three groups depending on the result of the tests: no evidence of glucose metabolism abnormality (controls); impaired glucose tolerance (IGT); and GDM. All three groups were evaluated for serum human advanced glycation end-products (AGEs) concentrations, carboxymethyl lysine (CML) concentration and receptor for advanced glycation end-product concentrations (RAGE/AGER), body mass index (BMI), age, fasting glucose levels, obstetrical parameters and gestational age. RESULTS: The study included 180 women divided into 59 (32.8%) GDM, 50 (27.8%) IGT and 71 (39.4%) controls. Age was similar among the three groups. Whereas fasting glucose levels and BMI in the three groups was significantly different, AGEs, CML, RAGE/AGER levels were found as significantly different between the groups (p<0.001). CONCLUSION: In this study the use of AGEs, CML, and RAGE/AGER concentrations for the diagnosis and screening of gestational diabetes was investigated. It was found that advanced glycation products were significantly elevated in pregnancies with both IGT and GDM. These biochemical markers of glucose homeostasis dysregulation may have potential for GDM screening in the future.